2005
DOI: 10.1038/nphys120
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-stimulated cooling of single atoms in three dimensions

Abstract: Taming quantum dynamical processes is the key to novel applications of quantum physics, e.g. in quantum information science. The control of light-matter interactions at the single-atom and single-photon level can be achieved in cavity quantum electrodynamics, in particular in the regime of strong coupling where atom and cavity form a single entity. In the optical domain, this requires permanent trapping and cooling of an atom in a micro-cavity. We have now realized three-dimensional cavity cooling and trapping… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
160
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(163 citation statements)
references
References 23 publications
2
160
0
1
Order By: Relevance
“…This is achieved by a combination of dipole trapping in two (or three) orthogonal blue or red detuned standing light waves [10] and cavity cooling [11,12] or, most recently, feedback cooling [13,14]. The standing light waves can spatially be adjusted in such a way that the atom is trapped at the desired position, as verified by means of a CCD camera which records fluorescence light emitted by the atom, for example during cooling intervals and state preparation.…”
Section: Single-atom Localizationmentioning
confidence: 99%
“…This is achieved by a combination of dipole trapping in two (or three) orthogonal blue or red detuned standing light waves [10] and cavity cooling [11,12] or, most recently, feedback cooling [13,14]. The standing light waves can spatially be adjusted in such a way that the atom is trapped at the desired position, as verified by means of a CCD camera which records fluorescence light emitted by the atom, for example during cooling intervals and state preparation.…”
Section: Single-atom Localizationmentioning
confidence: 99%
“…Systematic experimental studies of cavity-mediated laser cooling have subsequently been reported by Rempe and co-workers [3][4][5][6], Vuletić and co-workers [7][8][9][10], and others [11,12]. Recent atom-cavity experiments access an even wider range of experimental parameters by replacing conventional high-finesse cavities [13,14] with optical ring cavities [15,16] and tapered nanofibers [17,18] and by combining optical cavities with atom-chip technology [19,20], atomic conveyer belts [21,22], and ion traps [23].…”
Section: Introductionmentioning
confidence: 99%
“…Another example is connected to the so-called cavity cooling method which is suitable to complement the deep conservative potential of FORT by a damping force induced by the field of a high-finesse optical resonator [16,17]. Various cavity cooling setups have been realized: (i) the FORT field can be along the cavity axis and detuned from the near-resonant cavity field by several free spectral ranges [18,19]; or the FORT lasers can be perpendicular to the cavity axis with photons scattered into the cavity responsible for cooling [20,21]. The simultaneous cooling and trapping gives rise to very long trapping times for single atoms.…”
Section: Introductionmentioning
confidence: 99%